واقع التجارة الالكترونية في الشركات الصغيرة الحجم : دراسة ميدانية على عينة من الشركات التجارية في محافظة نينوى - علاء عبدالسلام يحيى; علاء احمد حسن الجبوري (PROSPECTIVE RESEARCHES, 2023)
The present research presents the real situation of electronic commerce in small companies taking into consideration the essential elements and the possibility of using them in commercial companies in Ninevah. It points out that the commercial companies use of the e- commerce to offer the products on the internet and negotiate with the buyers and the importers by the brokers. Bearing in mind the restricted use the commerce because of some obstacles such as the absence of financial cards which are necessary for commercial transactions and the lack of skill in using the computers, as well as the absence of legal environment to organize the application of this kind of commerce. This will, in turn, impose the use of electronic means of payment and there must be a need to think of having a legal framework for e- commerce .